Programa Residência Pedagógica: experiências dos estudantes-residentes do subprojeto de matemática em tempos de pandemia - Santana, Tailane de Jesus (2023)
This dissertation aims to understand how student-residents of the mathematics subproject/Pedagogical Residency Program (PRP) constituted themselves as teaching subjects through narratives about their experience during the pandemic. To this end, some conceptual tools proposed by Foucault are mobilized and the Pedagogical Residency is used as a device. Teacher training and the way in which Foucauldian tools influenced studies in the area of ​​Mathematics Education are discussed. We follow the paths proposed by Larrosa and Foucault to problematize the device of experience. It takes as a basis Foucault's ideas about biopower and biopolitics and observes how these concepts permeate the Pedagogical Residency and the pandemic. This is research with a qualitative approach, operationalized through the observation of fortnightly meetings and experience reports produced by student-residents as a calculation of the workload of the activities of the mathematics subproject within the scope of the Higher Education Institution (HEI) carried out in remote mode, due to the pandemic caused by the SARS-CoV-2 virus. In a complementary way, a documentary analysis of a corpus consisting of ordinances and notices is carried out. For data analysis, it is based on discourse analysis, with a Foucauldian approach. In view of this, three units of analysis are taken as a reference: the planning and constitution of the student-resident subject, the practices carried out by the student-resident subjects in training and the pedagogical experiences as well as the student-residents and the mathematical experiences. The results of this study contribute to expanding discussions on this topic in the academic community, highlighting the relevance of public policies for teaching degrees. It is noteworthy that the experiences lived by resident students, crossed by power-knowledge relationships during remote teaching, contributed to the training of future Mathematics teachers, even though traces of discontinuity were observed between face-to-face and remote teaching. However, it is shown, through pedagogical and mathematical experiences, the contributions of the PRP to the construction and constitution of the future teacher subject, especially the mathematics teacher, in a troubled period of their training process.